2002
DOI: 10.1093/ajcn/76.2.326
|View full text |Cite
|
Sign up to set email alerts
|

The n−3 fatty acids eicosapentaenoic acid and docosahexaenoic acid increase systemic arterial compliance in humans

Abstract: EPA and DHA increase SAC and tend to reduce pulse pressure and total vascular resistance, effects that may reduce the risk of adverse cardiovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
117
0
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(135 citation statements)
references
References 28 publications
9
117
0
6
Order By: Relevance
“…The result was consistent with other studies (McVeigh et al, 1994;Nestel et al, 1997Nestel et al, , 2002O'Keefe et al, 2006). Large arterial stiffening was associated with hypertension, but both are not identified.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The result was consistent with other studies (McVeigh et al, 1994;Nestel et al, 1997Nestel et al, , 2002O'Keefe et al, 2006). Large arterial stiffening was associated with hypertension, but both are not identified.…”
Section: Discussionsupporting
confidence: 92%
“…Clinical trials have showed that n-3 fatty acids (fish oil, flaxseed oil or purified eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA)) supplementation can improve arterial elasticity in normotensive subjects with dyslipidemia, obesity or diabetes (McVeigh et al, 1994;Nestel et al, 1997Nestel et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of dyslipidaemic subjects, supplemented with fish oil in a dose and in an intervention period comparable to the present, Nestel et al (2002) found a significant improvement of the systemic arterial compliance, which is a measure of the function of predominantly large elastic arteries. In the present study, arterial compliance was measured regionally, in predominantly medium-sized muscular arteries, without effect in either the TFA or the n-3 PUFA study group.…”
Section: Discussionsupporting
confidence: 75%
“…Long-chained n-3 PUFA have been shown to have positive effects on blood lipids, haemostasis, leukocyte and vascular function, arterial compliance (AC) and heart rate variability (HRV) (Christensen et al, 1999;Goodfellow et al, 2000;Nestel et al, 2002), the latter being a strong predictor of SCD (Curtis and O'Keefe Jr, 2002). Industrially produced TFA adversely influence blood lipids (Ascherio et al, 1999), as well as endothelial function (de Roos et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…They suggest that atherosclerotic plaques are responsive to dietary modification such as n-3 FA which will affect plaque stability. c) Blood pressure and platelet aggregation-N-3 FA alter vascular function by enhancing the release of nitric oxide (NO) [94,95], as well as modifying the release of ADP [96], decreasing vasoactive prostanoids (such as thromboxane A 2 which is a potent platelet aggregator and vasoconstrictor) [97] and improving arterial compliance [98]. Therefore n-3 FA can decrease blood pressure [99].…”
Section: Molecular Mechanism Of N-3 Fa Related To Cvdmentioning
confidence: 99%